Environmental risk assessment and source apportionment of heavy metals in soils and natural plants surrounding a cement factory in NE Iran - Yaser Safari; Mahboobeh Karimi (Advances in Environmental Technology, 2019)
Introducing different heavy metals (HMs) into the environment through cement production has been recognized as a serious concern globally. The present study was carried out to assess the environmental risk of chromium (Cr), nickel (Ni), lead (Pb), and cadmium (Cd) pollution in the soil and plants surrounding the Shahrood Cement Factory, Northeast Iran. A total of 35 surface soil samples (0–10 cm) and 23 natural plant samples were collected. After preparation, the soil samples and plant tissues were analyzed for their total concentration of Cr, Ni, Pb, and Cd. In addition to normal statistical analyses, the inverse distance weighting (IDW) method was applied to prepare the thematic distribution maps. The results showed that the total Cr, Ni, Cd, and Pb soil concentrations ranged from 4.19 to 21.74, 2.11 to 41.20, 0.77 to 4.23, and 2.72 to 54.50, respectively. Comparing the soil content of the studied HMs with their national threshold values revealed that except for Cd in limited locations, other HMs were substantially lower than their permissible limits, indicating that the area was not polluted. The spatial distribution maps of selected HMs suggested an anthropogenic source for elevated Pb and Cd soil concentrations, whereas Cr and Ni soil concentrations were influenced by both natural and anthropogenic factors. Furthermore, the relatively high Pb concentrations in the plant tissues implied the role of car exhaust in introducing this pollutant into the environment. Even though the environmental risk of HMs in the studied area currently appears to be low, preventing the adverse impacts of cement production in this area requires further precautions.